ANALISIS PROPERTI BAHAN BAKAR MINYAK DARI PLASTIK LDPE (LOW DENSITY POLYETHYLENE) DAN PET (POLYETHYLENE TEREPHTHALATE) MENGGUNAKAN PROSES PIROLISIS - Mietra Anggara; Ajie Prana Mesa; Bernadus Crisanto Putra Mbulu (Polinema Press, Politeknik Negeri Malang, 2022)
Plastic waste is an environmental problem that is hotly discussed in the era of globalization. Almost all people are starting to realize the dangers caused by environmental damage. The purpose of this study was to determine the properties of fuel oil resulting from the pyrolysis process for LDPE (Low Density Polyethylene) and PET (Polyethylene Terephthalate) plastics. The research method used is through experiments with the Pyrolysis process. In managing LDPE and PET plastic waste, namely the pyrolysis technique which can produce fuel oil. The types of plastic used in this study were LDPE plastic bags, garbage bags and PET juice plastic cups and mica plastic. This research was carried out using a temperature of 300 0C with a time of 1 hour and a mass of 1 kg of plastic to get different density results. The results showed that the plastic bag had an average value (density) of 0.929 g/mL, (viscosity) with an average of 0.565 m2/s and (Flash point) 410C, but the trash bag had an average (density) of 0.909 g/mL, (viscosity) with an average of 0.43 m2/s and (Flash point) 560C, then on plastic juice cups it has an average value (density) of 0.884 g/mL (viscosity) with an average of 0.575 m2/ s and (Flash point ) 350C, while mica plastic has an average density value of 1.074g/mL, (viscosity) with an average of 0.575 m2/s and (Flash point ) 420C. The results of pyrolysis of LDPE and PET plastic types are good fuels to use, namely pyrolysis fuel for PET plastic juice cups closer to premium, while the LDPE plastic type in the plastic bag category tends to be close to premium